ANALISIS TOKOH DAN PENOKOHAN DALAM NOVEL CINTA KITA YANG RASA (Karya Ariani Octavia) - Irwan Soulisa; Agustinus G Gifelem; Petter Manuputty (SOSCIED, 2020)
The purpose of this research is to describe: Analysis of the role of characters and characterizations in Ariana Octavia's Novel Cinta Kita Yang Rasa. This research is a descriptive qualitative research. The method used is descriptive method. The source of the data is Ariana Octavia's Novel, Analysis of Characters and Characteristics. 1st print and from the internet. Data collection techniques used reading and note-taking techniques. The data analysis technique used is the Seiddel via Maleong qualitative analysis which includes three components, namely data reduction, data presentation, and conclusion drawing. The research procedure consisted of several stages, namely data collection, data selection, analyzing the selected data, and making research reports. Based on the results of the research it can be concluded: in the novel Analysis of Characters and Characteristics in the Novel Cinta Kita Yang Rasa by Ariana Octavia wants to convey characters and characterizations that are very useful for readers by animating the contents of the stories in them, so that they can become more alive and add variety and avoid Monotonous things that can bore readers in the novel Analysis of Character and Characteristics in the Novel Cinta Kita Yang Rasa by Ariana Octavia.